The Existence of Women in the Novel Tuhan Izinkan Aku Menjadi Pelacur by Muhidin Dahlan: A Feminist Analysis - Yulistiana, Linda; Ulfiyani, Siti; Muhajir, Muhajir (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the existence of women in Muhidin Dahlan’s novel Tuhan, Ijinkan Aku Menjadi Pelacur (God, Let Me Become a Prostitute) using Simone de Beauvoir’s existentialist feminist perspective. The focus of the study is on the representation of female characters within patriarchal power relations, religious ideology, and social pressures that limit their freedom and autonomy. The purpose of this study is to describe the forms of female existence portrayed in the novel. The method employed is descriptive qualitative, with data collected through literature review and textual analysis. The analysis is conducted based on Beauvoir’s four strategies of female existence: women as workers, women as intellectuals, women as agents of social transformation, and women who reject otherness. The results indicate that the female characters experience objectification and subordination within the patriarchal system. However, through self-awareness, critical thinking, and reflective actions, they strive to escape these constraints and assert themselves as free subjects. This novel represents women’s struggles to construct their existence and freedom amid social and ideological pressures.